Comparative evaluation of sublay versus onlay meshplasty in incisional and ventral hernias - Dhaigude, B. D.; Sugunan, Aneesh; Pancbhai, S. V.; Francis, Merry; Patel, Keyur; Metta, Vipul (International Surgery Journal, 2017)
Background: Hernia derived from the Latin word, is a protrusion of a viscus or part of a viscus through an abnormal opening in the walls of its containing cavity. Objectives of present study were to evaluate sublay Vs onlay meshplasty in incisional and ventral hernia and to compare and determine duration of operation and hospital stay, post-operative complications and recurrences. Methods: The study was conducted at Dr. D. Y. Patil Medical College and Hospital, DPU University, for a period of 2 years (from July 2015 - September 2017) and is a prospective and comparative randomized type of study using 100 cases (Group A Onlay and Group B Sublay - 50 each). The study was approved by the Institute’s Ethics Committee. Results: 100 patients were operated in our study. In group B, the mean operative time [70.72±18.56], and in group A mean operative time (50.96±12.61). The duration of hospital stay was an of average 7.62±1.78 days in group B, and an average hospital stay of 8.84±1.89 in group A. Suture site infection was18%. group A (26%) and group B (12%). Seroma was seen in 5 patients, group A (8 %) and in group B (2%). Flap necrosis was 8% in group A and in 6% in group B. 10 patients had wound dehiscence, group A (14%) and group B (6%). 4 patients were reported with mesh infection (6%) in group A and (2%) in group B. Recurrence was 1% group A. Conclusions: Sublay meshplasty is good alternative to onlay meshplasty that may be applicable to all forms of ventral and incisional hernias. The mesh related complication rate and recurrence was found to be minimal.